Legal Analysis of Handling Action Criminal Corruption in Village Fund Management - Muhammad Ikram Alfareza; Nurul Qamar; Mursyid Mursyid (COMPENDIUM OF JUDGE MADE LAW, 2025)
This study aims to determine the system of handling cases of corruption of village funds at the District Attorney of Gowa Regency and what factors influence the handling of corruption of village funds at the District Attorney of Gowa Regency. This research uses empirical research methods conducted at the District Attorney of Gowa Regency. Primary and secondary data were obtained using various data collection methods, including interviews, and literature reviews conducted as part of the field study. The author will write a research report by clearly presenting the research findings, which will be drawn from descriptive and qualitative analysis of the data collected. The results of this study indicate that the case handling system for corruption of village funds at the District Attorney of Gowa Regency is considered to be quite optimal in handling corruption cases in Gowa Regency, although sometimes there are still obstacles in the process of handling this case, but the court is able to overcome them and influencing factors in the handling of corruption of village funds at the District Attorney of Gowa Regency, namely the lack of ability of village officials in handling finances, regulatory factors related to regulations governing villages, and community factors such as lack of supervision in the management of village funds. It is hoped that through regular training for village officials on financial governance, applicable regulations, and the preparation of transparent and accountable accountability reports, it can improve the understanding of village officials in carrying out their duties and it is hoped that the strengthening of internal supervision by APIP and community involvement in external supervision can increase the effectiveness of supervision of village fund management. In addition, it is expected that the development of a reporting system that is easily accessible and provides protection to reporters, can strengthen transparency and prevent misuse of village funds. With a good reporting mechanism, it is expected to create a more accountable and open system for the community.